Protective Efficacy of Different Live Attenuated Infectious Bronchitis Virus Vaccination Regimes Against Challenge With IBV Variant-2 Circulating in the Middle East - Sultan, Hesham A.; Ali, Ahmed; El Feil, Wael K.; Bazid, Abdel Hamid I.; Zain El-Abideen, Mohamed A.; Kilany, Walid H. (Frontiers in Veterinary Science, 2019)
Six vaccination regimes using classical (Mass-type) and variant (IB-VAR2 and IB-793B) live vaccines were evaluated against Middle Eastern variant-2 infectious bronchitis virus challenge. Six groups of SPF chicks (30 birds/group) were vaccinated using prime-boost regimes at day-1 and day-14 using; IB-M41:IB-VAR2, IB-VAR2:IB-VAR2, IB-VAR2:IB-M41, IB-Ma5:IB-793B, IB-793B:IB-793B, and IB-793B:IB-Ma5, respectively. Ciliostasis and lesion scores were evaluated at day-5 after each vaccination. Birds were challenged intranasally at 14-day post 2nd vaccination using 105EID50/0.1ml/bird of wild-type IBV (Eg/1212B/2012). At 3, 5, and 7-day post challenge (DPC) virus shedding was monitored by real-time RT-PCR. Five chicks/group were euthanized at 7DPC for ciliostasis and lesion scoring &, and histopathology was conducted on 3 chicks/group. Seroconversion was evaluated at 14 DPC. All groups primed with the 793B vaccine showed relatively higher ciliostasis scores compared to other groups. The IB-VAR2 vaccinated groups showed the highest protection rates (80-100%) and high protection score (67.6-73.2%) compared to the 793B vaccine groups (50-60%). The virus shedding was significantly reduced at 3 and 5DPC in groups received the IBV-VAR2 (prime or booster) compared to those received the 793B vaccine. In conclusion, the homologous IBV-VAR2 vaccine showed superior results compared to 793B or Mass-type vaccines confirming the importance of IBV vaccine seed homology to the circulating IBV strains.